Sustainable valorization approaches on crustacean wastes for the extraction of chitin, bioactive compounds and their applications - A review - Nur Izyan, Wan Azelee; Dahiya, Digvijay; Ayothiraman, Seenivasan; Norhayati, Mohamed Noor; Zaitul Iffa, Abd Rasid; Aizi Nor Mazila, Ramli; Ravindran, Balsubramani; Iwuchukwu, Felicitas U.; Selvasembian, Rangabhashiyam (Elsevier Ltd, 2023)
The unscientific disposal of the most abundant crustacean wastes, especially those derived from marine sources, affects both the economy and the environment. Strategic waste collection and management is the need of the hour. Sustainable valorization approaches have played a crucial role in solving those issues as well as generating wealth from waste. The shellfishery wastes are rich in valuable bioactive compounds such as chitin, chitosan, minerals, carotenoids, lipids, and other amino acid derivatives. These value-added components possessed pleiotropic applications in different sectors viz., food, nutraceutical, cosmeceutical, agro-industrial, healthcare, and pharmaceutical sectors. The manuscript covers the recent status, scope of shellfishery management, and different bioactive compounds obtained from crustacean wastes. In addition, both sustainable and conventional routes of valorization approaches were discussed with their merits and demerits along with their combinations. The utilization of nano and microtechnology was also included in the discussion, as they have become prominent research areas in recent years. More importantly, the future perspectives of crustacean waste management and other potential valorization approaches that can be implemented on a large scale.